Authoritarian Parenting Is Assoociated With Bullying Behavior In Teenagers At Smp Negeri 1 Namorambe, Deli Serdang Distriet In 2023 - Tane, Reisy; Angriawan; Herri Novita Br Tarigan; Tahnia Yuliend Mianauli (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Adolescence is a period of rapid physical, psychological, and intellectual growth and development. Bullying is an aggressive action that one person repeatedly takes against another, causing physical or mental harm to the victim. Authoritarian parenting style emphasizes the importance of children obeying all parental rules. The study involved 86 students as study subjects, selected using non-probability sampling with the purposive sampling technique. Data collection in this study used a parenting style scale based on the Parental Authority Questionnaire (PAQ) and a bullying behavior scale based on the Bullying Questionnaire by Putri (2018). These data were subsequently analyzed using the Chi-square test, yielding a result of CI = 0.001. The hypothesis was tested using a Cross-Sectional correlation. The correlation coefficient obtained r = 0.306 with a significance of 0.004 ). The study results indicated a positive relationship between the tendency of bullying behavior and authoritarian parenting style at SMP Negeri 1 Namorambe. As the authoritarian parenting style increases, the incidence of bullying behavior also increases. Conversely, the authoritarian parenting style decreases, the incidence of bullying behavior decreases as well. In conclusion, this study reveals a moderate positive relationship between authoritarian parenting style and bullying behavior among adolescents at SMP Negeri 1 Namorambe in 2023.